Violation Of Human Rights Reflected In Malala Yousafzai & Christina Lamb's I Am Malala (2013) Memoir: A Sociological Approach - Lestari, Niken; , Dr. Phil. Dewi Chandraningrum, M.Ed; , Titis Setyabudi, S.S. M.Hum (2015)
The major problem of this study is violation of human rights, all people in this world have same rights which is called human right. Human rights are rights that inherent to all human beings, whatever our nationality, place of residence, sex, national or ethnic origin, color, religion, language, or any other status. Violation of human rights is an action that breaks human rights and violate universally agreed international human rights standards, such as child trafficking, child labor, rekigious violation, discrimination, etc. The objective of this study is to analyze Malala Yousafzai and Christina Lamb's I Am Malala based on the structural eements and analyze this memoir based on the Sociological Approach The writer employs qualitative method. The writer uses two data sources: primary and secondary. The primary datasource is about the memoir itself. Then, the secondary data sources are the books about sociological, references from internet about I Am Malala, and other sources, which have relation to the analysis. The method of data collection is library research and the technique of data collection is descriptive technique. Based on the anaylisis, the writer gets some conclusions. The study shows that the problem faced by the minor character and major character. It is proved by the conditions in Pakistan, there are many violations and discriminations. This violations happened because we didn't respect each other. So as a human, we must respect ecah other because we have same rihts in ths world.